Daith Ear Piercing and Migraine Symptoms - Blatchley, Chris; Wilkins, Arnold (British Journal of Healthcare and Medical Research, 2023)
We report the initial results from an ongoing study of Daith ear piercing undertaken in collaboration with experienced piercers at a long-established national chain of piercing studios. Daith piercing passes through the cartilage of the crus helix, an area innervated by the auricular branch of the vagus nerve. Historically, Daith piercing was cosmetic, but has become increasingly popular after unexpected improvement in migraine was first noticed in 1992. Since then, many migraine sufferers have sought a Daith piercing from cosmetic piercing studios and their reports of improvements continue. Apart from isolated case histories there has been no medical investigation. Electrical stimulation of the vagus nerve is an established treatment for migraine and epilepsy that is recognised by NICE in the UK. We hypothesize that the piercing stimulates the vagus nerve by mechanical or inflammatory irritation.